Financial inequality nexus and Islamic banking - Diyah Putriani; Prastowo Prastowo (Jurnal Ekonomi & Keuangan Islam, 2019)
This research aims to investigate the role of Islamic banking on income inequality reduction. The data of this research spans from 2010 to 2015 and investigate 49 Islamic banks from 13 selected countries. This study employs Panel data EGLS. To compare with other macroeconomic variable, this research involves GDP Per capita, and inflation as control variable. The estimation result shows that financial depth measured by total customer deposit to GDP ratio has negative relationship with income inequality. It perhaps occurs when there is an increase in income, customers prefer to save their additional income in Islamic banks. As customers increase their deposits, Islamic banks enlarge its financing on the prospect entrepreneurs. These entrepreneurs, afterwards, may expand their business and create new jobs. More new jobs offer means more people get stable income and as a result may reduce income inequality in the society.